The Impact of Teaching Aids on The Academic Performance of Learners in Natural Science - Nghitoolwa, Hilya Tulipomwene Shuulinawa; Chirimbana, Moses; Medusalem , Medusalem (Journal of Education For Sustainable Innovation, 2024)
This qualitative study explores the impact of teaching aids on the academic performance of seventh-grade natural science learners at a selected school in the Kunene Region. The research focuses on understanding how instructional aids affect student comprehension, engagement, and overall academic achievement. A purposive sampling technique was used to select 10 seventh-grade students and two science teachers for semi-structured interviews, providing in-depth insights into their experiences with teaching aids in the classroom. Data were analyzed thematically, revealing key subthemes that illustrate the positive effects of teaching aids on learning outcomes. Results indicate that teaching aids, such as charts, models, and laboratory equipment, enhance understanding of concepts, increase student engagement, improve academic performance, promote critical thinking, and foster collaborative learning. However, the study acknowledges a significant limitation: its focus on a single region, which limits the generalizability of the findings to other contexts. Recommendations for educators and policymakers include investing in a variety of teaching aids, incorporating interactive learning techniques, and fostering collaborative learning environments. The study also suggests further research with larger sample sizes, across multiple regions, and using quantitative methods to validate and expand on these findings. Additionally, a longitudinal approach to understanding the long-term impact of teaching aids on educational outcomes is proposed as an area for future study. The insights gained from this study contribute to the ongoing discourse on effective teaching practices and underscore the importance of providing adequate resources to support natural science education.